A novel RASA1 mutation causing capillary malformation–arteriovenous malformation (CM–AVM) presenting during pregnancy. Issue 7 (17th May 2013) - Durrington, Hannah J.; Firth, Helen V.; Patient, Charlotte; Belham, Mark; Jayne, David; Burrows, Nigel; Morrell, Nicholas W.; Chilvers, Edwin R.
ABSTRACT Capillary malformation–arteriovenous malformation (CM–AVM) is a newly recognized clinical entity caused by mutation of the RASA1 gene, which encodes p120‐RasGAP. Here we describe, for the first time, a patient with CM–AVM presenting during the late stages of pregnancy with pulmonary "capillary level" microvascular shunt, worsening cutaneous capillary malformations, and gross fluid overload. Sequencing revealed a novel mutation of the RASA1 gene involving a frameshift mutation in the RASGAP domain of RASA1. This report extends our current genetic and clinical understanding of CM–AVM. © 2013 Wiley Periodicals, Inc.